PEMAHAMAN KONSEP DAN HOTS PADA PEMBELAJARAN THINK PAIR SHARE BERBANTUAN LKPD BERBASIS AL-QUR'AN DITINJAU DARI MINAT BELAJAR - Asih, Ayu Mustika; Anggoro, Bambang Sri; Dewi, Novian Riskiana (De Fermat : Jurnal Pendidikan Matematika, 2026)
This study aimed to determine the effect of the Think Pair Share (TPS) learning model assisted by Al-Qur'an-based Student Worksheets (LKPD) on students' conceptual understanding and Higher Order Thinking Skills (HOTS) in terms of their learning interest. This study employed a quasi-experimental method using a posttest-only control group design. Data were collected through tests of conceptual understanding ability, HOTS tests, and learning interest questionnaires, and were analyzed using a two-way Multivariate Analysis of Variance (MANOVA). The results showed that the learning model had a significant effect on students' conceptual understanding and HOTS, with a significance value of 0.000. Learning interest also had a significant effect on students' conceptual understanding and HOTS (sig = 0.014), indicating that students with different levels of learning interest demonstrated different levels of achievement. Furthermore, there was an interaction effect between the learning model and learning interest on students' conceptual understanding and HOTS (sig = 0.020). Therefore, the TPS learning model assisted by Al-Qur'an-based LKPD was effective in enhancing students' conceptual understanding and HOTS when viewed from the perspective of their learning interest.